The association of BMI and social distance towards obese individuals is mediated by sympathy and understanding. (March 2015) - Sikorski, Claudia; Luppa, Melanie; Angermeyer, Matthias C.; Schomerus, Georg; Link, Bruce; Riedel-Heller, Steffi G.
Abstract: The desire for social distance towards individuals with obesity as part of the stigmatization process has not been investigated. The aims of this study include: (a) determining the prevalence of social distance and its domains in a population-based sample; (b) reporting levels of emotional response; and (c) investigating the association of BMI, emotional response and social distance. The data were derived from a large population based telephone survey in Germany (total n = 3, 003, this sub-sample n = 1008). Emotional response to individuals with obesity was assessed for the emotions discomfort, pity, insecurity, amusement, sympathy, help and incomprehension (5-point Likert scale). Social distance was measured on a 5-point Likert scale covering different areas of social interaction. This served as the dependent variable for a linear regression model and mediation models that included BMI and emotional response. Social distance was highest for job recommendation, introduction to a friend, someone with obesity marrying into the family and renting out a room. Means of emotional responses were highest for pity (Mean = 2.58), sympathy (Mean = 2.87) and wanting to help (M = 2.76). In regression analyses, incomprehension (b = 1.095, p < 0.001) and sympathy (b = −0.833, p < 0.001) and the respondents' own BMI (b = −0.145, p < 0.001) were significantly associated to the overall amount of social distance. Mediation models revealed a significant mediation effect of BMI through sympathy (b = −0.229, % of total effect through mediation = 10.3%) and through incomprehension (b = −0.057, % of total effect through mediation = 27.5%) on social distance. Social distance towards individuals with obesity is prevalent in the general public in Germany and it is associated with emotional responses. Altering the emotional responses may, therefore, be a starting point in anti-stigma interventions. Evoking sympathy and lowering incomprehension may result in lower overall social distance. Highlights: Population-based prevalence rates of social distance towards obesity are provided. Prevalence rates are compared to other illnesses, such as mental disorders. Emotional responses to individuals with obesity are described. Personal Interaction, sympathy and understanding affect social distance.